The Contribution of Islamic Philosophy and the Implementation of Islamic Education in Realizing Democratic Elections in Indonesia - Rijal, Syamsul; Pranajaya, Syatria Adymas (Jurnal Pemikiran Islam, 2025)
This article examines the contribution of Islamic philosophy and Islamic education to the realization of democratic elections in Indonesia. The study aims to analyze how the core principles of Hablum Minallah (tauhid and taqwa) and Hablum Minannas (adl, shura, and amal makruf nahi munkar) provide ethical and normative foundations for political participation and the strengthening of democratic values. A qualitative approach with normative-philosophical analysis is employed. Data are collected through a comprehensive literature review, including classical and contemporary Islamic philosophical works, relevant legal and policy documents, and studies on Islamic education and democratic practices. Thematic and normative analysis is used to synthesize and connect philosophical values with educational strategies and electoral ethics. The analysis shows that integrating Islamic philosophical values into educational practices—through curriculum development, extracurricular activities, and community-based da’wah and counseling—can enhance civic awareness, foster responsible citizenship, and promote integrity in the electoral process. Regulatory support from national educational policies further reinforces these efforts. Islamic education is identified as a vital mechanism for instilling democratic culture, ethical conduct, and resilience against challenges such as misinformation and identity politics. The findings suggest practical strategies for policymakers and educators to incorporate Islamic values into educational programs, aiming to support ethical democratic participation. These include curriculum integration, interactive civic education, digital literacy training, and targeted community engagement. This study offers an integrative framework that connects Islamic philosophical, normative, and educational dimensions to the practical challenges of democracy in Indonesia. By situating Islamic education as both doctrinal transmission and civic empowerment, the research provides a reference for further study and policy development at the intersection of religion, education, and democratic culture.